Adherence to reporting guidelines and clinical trial registration policies in oncology journals: a cross-sectional review. Issue 3 (13th April 2018) - Wayant, Cole; Moore, Gretchan; Hoelscher, Mark; Cook, Courtney; Vassar, Matt
Abstract : Reporting guidelines (RG) aim to improve research transparency and ensure high-quality study reporting. Similarly, clinical trial registration policies aim to reduce bias in results reporting by ensuring prospective registration of all trial outcomes. Failure to adhere to quality standards documented in RGs may result in low-quality and irreproducible research. Herein, we investigate the adherence to common RGs and trial registration policies in 21 oncology journals. We surveyed the Instructions for Authors page for each of the included oncology journals for adherence to common reporting guidelines and trial registration policies. We corresponded with editors to determine accepted study types and cross-referenced this information with a journal's RGs and trial registration policies to calculate the per cent of journals that adhere to a specific guideline or policy. 76.2% (16/21) of oncology journals surveyed adhere to Consolidated Standards of Reporting Trials guidelines for clinical trials while only 33.3% (7/21) adhere to Strengthening the Reporting of Observational Studies in Epidemiology for observational studies. Similarly, 76.2% (16/21) of oncology journals adhere to clinical trial registration policies. We further demonstrate that journal adherence to RGs positively affects author reporting, despite adherence to trial registration policies showing no such benefit. Our results show that oncology journals adhere to RGs and trial registration policies at a higher rate than other specialties, but nonetheless show room for improvement. We conclude that oncology journal adherence to RGs and trial registration policies is encouraging, but nonetheless suboptimal. We recommend the adoption of RGs and trial registration policies by all oncology journals.